Formulasi dan Uji Antijerawat Gel Ekstrak Etanol 70% Buah Belimbing Wuluh (Averrhoa Bilimbi Linn.) terhadap Bakteri Propionibacterium acnes - Azis Ikhsanudin; Siti Mardhiyah (Halu Oleo University, 2017)
ABSTRACT Belimbing wuluh fruit known have flavonoids that has a function as natural anti bacterial for acne treatmeant. To easer in using it, so it formulated in the form of gel. The aims of research was to know the influence of variation concentration ethanol extract 70% belimbing wuluh fruit to physical characteristic of gel and antibacterial activity of Propionibacterium acnes which a bacteria causes acne. Belimbing wuluh fruit extract was obtained by maceration. Extract formulated in the form of gel with variation concentration 4,17%w/v, 8,33% w/v, 12,5%w/v, 16,67%w/v, and 20,83%w/v. Antibacterial activity test was conducted by cup plate technique difusion methode and physical characteristic test covered organoleptic test, spreadibility test, and adhesivity test. The result of antibacterial test and physical characteristic test were analyzed statistically using Kruskall Wallis test and Mann Whitney test with 95% level confidence. The result of research showed that with an increasing concentration of extract could affect physical characteristic of gel and will increase antibacterial activity. The higher concentration extract, the color of gel obtained more concentrated, pH of gel be acid, decreasing adhesive power, spread power obtained smaller and inhibition diameter obtained bigger. The result of research obtained that formula 2 was a good formula with pH value 5, average adhesive power was 4,63 seconds ± 0,57, average spread power was 11,34 cm2 ± 0,44 and average diameter obstruent was 5 mm ±1,41. Based on the research could be concluded that gel extract ethanol 70% belimbing wuluh (Averrhoa bilimbi Linn) fruit had antibacteria activity against Propionibacterium acnes. Minimal concentration which could inhibit growth that bacteria found at concentration 5% and formula which had a good physical characteristic at formula 2.Keywords : Gel, Etanolic extract 70%; Averrhoa Bilimbi Linn, Propionibacterium acnes.